PENGUATAN KAPASITAS KELEMBAGAAN UPTD PERLINDUNGAN PEREMPUAN DAN ANAK (UPTD-PPA) TERHADAP PENINGKATKAN JEJARING PENANGANAN KEKERASAN DALAM RUMAH TANGGA DI KOTA SEMARANG - Angela - Novita; Puji - Astuti; Neny - Marlina (Journal of Politic and Government Studies, 2023)
The Regional Technical Implementation Unit for Women and Child Protection (UPTDPPA) in Semarang City is one of the institutions that provide protection and handling services for violence in Semarang. Domestic violence is predominantly experienced by women and children, necessitating effective, efficient, and comprehensive interventions. However, in its implementation, UPTDPPA in Semarang City faces challenges related to human resources, particularly the lack of capacity among support officers to provide legal information. This research utilizes a qualitative method to provide a comprehensive understanding of the situation and conditions of capacity strengthening within the UPTD-PPA in Semarang City. The findings of the research indicate that the capacity enhancement of UPTDPPA in Semarang City lacks planning and improvement concepts. Attention from the government is required in terms of human resources, organization, and budget dimensions. On the other hand, infrastructure and network dimensions have shown considerable improvement and progress.